Continuous production of biodiesel via transesterification from refined bleached & deodorized (RBD) palm oil - Muhammad Uzair Ahmad Jais (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Due to the demand of the petroleum based diesel in the worldwide country, biofuel has gained attention because it is made from renewable sources. Biodiesel was categorized as the green fuel which is safe for the environment and can be used as main energy sources. Sodium metal reacts with mathanol to produce sodium methoxide and used insitu as reagent to achieve higher amount biodiesel produce in term of FAME conversion due to no by product formation. A systems for continuous transesterification of RBD Palm Olein using laboratory apparatus was develop. In this study, the reaction was carried out using three values of methanol to RBD palm oil ratio (3:1, 6:1, 9:1) , three different reaction time 40 min, 60 min, 80 min) and three different temperature of the reaction (40c, 50c, 60c).